2005
DOI: 10.1002/ajmg.a.30813
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis-Noonan syndrome: Molecular evidence of the concurrence of both disorders in a patient

Abstract: Noonan syndrome (NS) is an autosomal dominant disorder characterized by short stature, facial anomalies, webbed neck, sternal deformity, heart defects, and, in males, cryptorchidism. PTPN11 encodes SHP2, an important component of several signal transduction pathways that acts as a positive regulator of RAS-mitogen activated protein kinase signaling. Neurofibromatosis type 1 (NF1) is another autosomal dominant disorder characterized by hamartomas in multiple organs. The NF1 gene encodes a GAP-related protein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
67
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 28 publications
9
67
0
2
Order By: Relevance
“…12 It is likely that the athypical symptoms observed in this patient resulted from the additive effect of two mutations affecting different genes, as reported in some subjects with neurofibromatosis-Noonan syndrome (MIM #601321). 15,16 These observations are in line with the present findings pointing to an association between c.5425C4T change and facial features of NS, including ptosis, low-set posteriorly rotated ears, hypertelorism, short neck and triangular face. Although none of the patients exhibited PVS, accurate cardiac screening on larger cohorts might be considered to assess whether the c.5425C4T substitution results in a higher risk of developing PVS or other congenital heart diseases.…”
Section: Discussionsupporting
confidence: 92%
“…12 It is likely that the athypical symptoms observed in this patient resulted from the additive effect of two mutations affecting different genes, as reported in some subjects with neurofibromatosis-Noonan syndrome (MIM #601321). 15,16 These observations are in line with the present findings pointing to an association between c.5425C4T change and facial features of NS, including ptosis, low-set posteriorly rotated ears, hypertelorism, short neck and triangular face. Although none of the patients exhibited PVS, accurate cardiac screening on larger cohorts might be considered to assess whether the c.5425C4T substitution results in a higher risk of developing PVS or other congenital heart diseases.…”
Section: Discussionsupporting
confidence: 92%
“…The authors concluded that the p.G409A mutation in the PTPN11 gene represents a mild partial mutation, acting as a modifier. On the other hand, the report of two pathogenic mutations in patients presenting neurofibromatosis-Noonan syndrome (NFNS) have been previously described (31,32) but in both cases one of the parents had one of the mutations, which increases the chance of this occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NF1 and NS have previously been found to coexist in the same patient. 19 No PTPN11, KRAS, RAF1, or SOS1 codingsequence mutations were found in the reported patient. However, mutations of these four genes account for only about 80% of NS cases, meaning that we cannot formally rule out the co-occurrence of NS and NF1 in the reported patient, despite our extensive molecular studies.…”
Section: Discussionmentioning
confidence: 73%